PENILAIAN KEEFEKTIVAN KEGIATAN PELATIHAN DALAM MEMANAJEMEN STRESS DALAM BEKERJA PADA BASARNAS SIBOLGA - Monica Amelia Dias Purba; Susilawati (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2023)
The purpose of this study was to see what the level of work stress was for members of National Search and Rescue Agency for Sibolga City before being given training, and after being given training on stress management. Furthermore, the research also highlighted whether there was an effect of stress management training on reducing work stress on members of National Search and Rescue Agency for Sibolga City. The method used in this study is a quantitative method of experimental design with the analysis technique of the T-test with paired sample T-test processed with SPSS version 20.0 for windows. The independent variable in this research is stress management training and the dependent variable is job stress. The population of this study are members of the National Search and Rescue Agency for Sibolga City. Sampling used purposive sampling while data collection techniques in this research used a psychological measuring instrument in the form of a scale, the work stress scale totaling 24 items. The results showed that before being given stress management training, 4 members of the National Search and Rescue Agency for Sibolga City had a high level of stress, and 4 people in the medium category. After being given stress management training, the stress level of BASARNAS members in Sibolga City decreased by 5 people in the medium category, and 3 people in the low category. Stress management training is effective in reducing work stress for members of the National Search and Rescue Agency for Sibolga City as evidenced by the significant index results of 0.000 (<0.050). Similar training in areas of work with potentially high levels of work stress is recommended to be implemented so that employee performance can be optimized due to efforts to manage employee stress